Activation of a Carbon Support Through a Two‐Step Wet Oxidation and Highly Active Ruthenium–Activated Carbon Catalysts for the Hydrogenation of Benzene. Issue 2 (27th December 2013) - Li, Ying; Lan, Guojun; Feng, Guoquan; Jiang, Wei; Han, Wenfeng; Tang, Haodong; Liu, Huazhang
Abstract A two‐step liquid oxidation approach was developed for the activation of carbon materials. Following nitric acid treatment and subsequent liquid oxidation by a mild oxidant such as H2O2, the number of surface acidic functional groups was increased without destroying the physical structures of the carbon materials. Ruthenium catalysts supported on activated carbon prepared by this two‐step liquid oxidation method show significantly improved Ru dispersion and excellent catalytic performance in the hydrogenation of benzene. The dispersion of ruthenium and the catalytic performance of Ru/activated carbon increases monotonically with the amount of surface functional groups.